Analisis Prediksi Pasokan Tandan Buah Segar (TBS) untuk Produksi Crude Palm Oil (CPO) Menggunakan Metode Holt Winters di PT. Teupin Lada - Lyra Julia Hapsari Harahap; Diana Khairani Sofyan; M Sayuti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
The palm oil industry is a strategic sector in Indonesia; therefore, the sustainability of Fresh Fruit Bunches (FFB) supply is a crucial factor in maintaining the continuity of Crude Palm Oil (CPO) production. PT Teupin Lada experiences uncertainty in FFB supply due to its dependence on external suppliers without fixed contracts, which leads to raw material downtime and reduced operational efficiency. This study aims to forecast FFB supply and to formulate supply security strategies based on the forecasting results. The Holt–Winters method is employed because it can accommodate trend and seasonal patterns in time series data. The data analyzed consist of historical FFB supply data from January to December 2024. Forecasting accuracy is evaluated using the Mean Absolute Percentage Error (MAPE). The results indicate that FFB supply exhibits a seasonal pattern. The additive Holt–Winters model provides the best performance, with a MAPE value of 6.28%. The forecasting results are then used as a basis for developing supply security strategies, including minimum supply contracts, seasonal incentives, and backup suppliers.